Konsentrasi belajar pada remaja putri: Kaitannya dengan kebiasaan sarapan dan status gizi - Syarifuddin, Rahmawati; Hafid, Wahyuni; Hano, Yanti Hz (UHAMKA PRESS, 2024)
Indonesia is in 65th place out of 130 countries, and the average quality of Indonesian human resources is still relatively low. Improving the quality of human resources can be done by optimizing the learning process of children and teenagers during school, where the factor that can increase the success of this process is having good learning concentration. The research aimed to determine factors related to female students' learning concentration at SMA Negeri 2 Limboto, Gorontalo Regency in 2023. This type of research was an analytical and observational study with a cross-sectional design. The population was female teenagers totaling 523 with a sample size of 235 female students. This research was conducted on May - November 2023 at SMA Negeri 2 Limboto, Gorontalo Regency. The instruments used were questionnaires and measuring instruments in the form of microtoices, digital Hb meters, digital scales, and the Food Frequency Questionnaire (FFQ), then analyzed using the chi-square test and presented in table form. Based on the results of the analysis, the chi-square test showed that there was a relationship between breakfast habits (p=0.002) and hemoglobin (Hb) levels (p=0.014) on study concentration, while nutritional status (BMI) (p=0.146) and MUAC (p=0.30) are not factors related to female students' study concentration at SMA N 2 Limboto in 2023. Female students are expected to be able to routinely measure their weight, height, and mid-upper-arm circumference (MUAC) at least once a month.